Reasons for Adoption and Non-adoption of Direct Seeded Rice in Punjab - Kaur, Kamalpreet; Kaur, Prabhjot (Indian Journal of Extension Education, 2017)
Direct seeded rice (DSR) technique is becoming popular nowadays because of its low-input demanding nature. There are  many reasons which motivated the respondents for adoption of direct seeded rice such as water saving, labour saving and  profitable technique etc. All the respondents started direct seeded rice because it gives better results than transplanting  method. To study the reasons of adoption and non-adoption of DSR, the study was conducted in five districts of Punjab;  Moga, Mukatsar Sahib, Faridkot, Sangrur and Patiala. From each district one village and from each village 15 farmers of  DSR and 15 of transplanting were selected by using random sampling technique. Data were collected by using personal  interview method. The data reveal that 98.67 per cent of the respondents started DSR as it saves time spent on paddy  nursery and reduce the transplanting cost. Whereas 97.33 per cent desired to save water and reducing labour cost, easy  practice which did not need puddling exercise and 96 per cent of the respondents showed their interest in DSR and adopted  the DSR technique. For the non-adoption of DSR, 90.67 per cent of the respondents reported that there was high risk to  crop in DSR. Whereas 89.33 per cent reasoned non-adoption due to non-availability of DSR drill and 88 per cent for  germination failure of direct seeded crop and due to more requirement of weedicide.
Keywords: Direct seeded rice; Resource conservation; Reasons; Weeds; Adoption